Breakthrough Listen – A new search for life in the universe. (October 2017) - Worden, S. Pete; Drew, Jamie; Siemion, Andrew; Werthimer, Dan; DeBoer, David; Croft, Steve; MacMahon, David; Lebofsky, Matt; Isaacson, Howard; Hickish, Jack; Price, Danny; Gajjar, Vishal; et al.
Highlights: Guidance in SETI can be found via probabilistic argument of the Drake Equation. SETI search methods with radio and near-IR/optical observations are proposed. Sky survey with telescope arrays utilizing beamforming technologies is proposed. Commensal telescope strategy during other astronomy observations is proposed. An open data strategy provides peer review of data analysis and results.